Gender and Connections among Wall Street Analysts - Fang, Lily Hua; Huang, Sterling (Review of Financial Studies, 2017)
We examine how alumni ties with corporate boards differentially affect male and female analysts’ job performance and career outcomes. Connections improve analysts’ forecasting accuracy and recommendation impact, but the effect is two to three times as large for men as for women. Connections also contribute to analysts’ likelihood of being voted by institutional investors as “star” analysts, but act as a partial substitute to performance for men, while a complement to performance for women. Our evidence indicates that men benefit more than women from connections in both job performance and the subjective evaluation by others.Received August 27, 2015; editorial decision January 24, 2017 by Editor Francesca Cornelli.